2009 European Conference on Radiation and Its Effects on Components and Systems 2009
DOI: 10.1109/radecs.2009.5994665
|View full text |Cite
|
Sign up to set email alerts
|

Bias effects on total dose-induced degradation of bipolar linear microcircuits for switched dose-rate irradiation

Abstract: Accelerated test techniques are needed in order to qualify bipolar devices intended for use in low dose rate environments. Indeed, low dose rate is known to enhance degradation of bipolar devices. Moreover, the bias of microcircuits is known to play a significant role in device degradation. In this work, bipolar microcircuits are irradiated with different bias configurations during the irradiation. It is shown that the bias configuration leading to the worst-case degradation is dose-rate dependent. Moreover, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…It is generally assumed that the irradiation with all pin GND is considered as the worst case, but as shown in [7]- [9], this is not always the case. Velo et al [9] have shown the impact of the bias configuration by running test on a COTS LM124 operational amplifier. Those tests highlighted the fact that not all of the parameters of a linear device see their sensitivity increase when GND.…”
Section: B Total Ionizing Dose Irradiationmentioning
confidence: 99%
“…It is generally assumed that the irradiation with all pin GND is considered as the worst case, but as shown in [7]- [9], this is not always the case. Velo et al [9] have shown the impact of the bias configuration by running test on a COTS LM124 operational amplifier. Those tests highlighted the fact that not all of the parameters of a linear device see their sensitivity increase when GND.…”
Section: B Total Ionizing Dose Irradiationmentioning
confidence: 99%